Water demand and use: Tunisia - Belhaj Fraj, Makram; Bergaoui, Karim; Gafsaoui, Y.; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
The Water Use Tool (WUT) assesses seasonal irrigation water consumption in the Bouheurtma Irrigation Scheme, using WaPOR data to provide historical and real-time statistics through an accessible interface for non-technical decision-makers.